SISTEM PAKAR DIAGNOSA PENYAKIT IBU HAMIL MENGGUNAKAN METODE CERTAINTY FACTOR (CF) UNTUK MENURUNKAN RISIKO KEMATIAN IBU HAMIL BERBASIS ANDROID - Aliy Hafiz; Ferry Susanto; Donny Muda Priyangan; Chandra Kirana (Jurnal informasi dan komputer, 2022)
An expert system is a system that seeks to adopt human knowledge into computers, so that computers can solve problems as experts do. The experts here are doctors and midwives. With a combination of technology and experts, pregnant women don't have to bother for consultations because they simply use the expert system found on Android-based cellphones. This study started from observations to collect data on complaints of pregnant women as a basic material in designing an expert system then interviews to collect information from doctors or midwives on duty whose information will be used as symptom and disease data.